KOMPETENSI DIGITAL SEBAGAI PILAR PROFESIONALISME GURU SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Sahbana Ridha; Difa Maulidya; Khairati Olfah; Aslamiah Aslamiah; Audia Mecca (Jurnal Manajemen Pendidikan, 2026)
Digital competence of primary school teachers is a critical prerequisite for effective 21st-century learning. Mastery levels in Indonesia remain variable and suboptimal, underscoring the need to identify key determinants and barriers for targeted intervention design. Objective: To synthesise empirical evidence on factors influencing teachers’ digital competence in Indonesia and the barriers and enablers in its development. Methods: Systematic Literature Review following PRISMA 2020. Searches of Scopus and Web of Science (2020–2026) applied inclusion criteria grounded in TPACK, DigCompEdu, and TAM frameworks. Results: Four determinants were identified: (1) attitude towards technology the strongest predictor, outweighing demographic variables; (2) professionalism and TPACK dominant predictor of technology-use intention; (3) digital analysis the most critical technological knowledge dimension; and (4) school curriculum support. Primary barriers include inadequate infrastructure, non-integrative training, and computer anxiety. Effective enablers comprise TPACK-based CPD, active professional digital communities, and intrinsic motivation. Conclusion: Advancing primary school teachers’ digital competence demands an ecosystemic approach integrating TPACK-based holistic CPD, constructive professional communities, and equitable digital infrastructure policy. Attitude and self-efficacy interventions consistently outperform isolated technical training.